Correlation Between Omega-3 Fatty Acids Plasma Levels with Muscle Mass and Handgrip-Muscle Strength in Head Neck Cancer Patients Undergoing Radiotherapy in Ciptomangunkusumo Hospital Jakarta - Elfina Rachmi; Inge Permadhi; Angela Giselvania (World Nutrition Journal, 2019)
Background. Cancer cachexia is common in head neck cancer caused by increasing proinflammatory cytokines, has effect on hipermetabolism, increased nutritional needs, anorexia, decreased muscle mass and body weight. Omega-3 fatty acids play a role in reducing inflammation, improving muscle mass and handgrip.Objective. This cross sectional study conducted in Department of Radiotherapy Dr. CiptoMangunkusumo Hospital, aimed to investigate correlation between omega-3 fatty acids plasma with muscle mass and hand grip-muscle strength in head neck cancer subjects undergoing radiotherapy.Method. This study was conducted from June to August 2016. The subjects were head neck cancer patients in stage I‒IV (18–65 years old) and had received >25 times radiation, and  obtained by consecutive sampling method. Total omega-3 fatty acids intake was obtained by semiquantitative Food Frequency Questionnaire. Anthropometric measurements used ShorrBoard and Smic® ZT-120, muscle mass used Omron HBF375®, and handgrip used Jamar® dinamometer. Omega-3 fatty acids plasma were examined by gas chromatography flame ionized detector. Correlation omega-3 fatty acids plasma with muscle mass were analyzed by Pearson, and correlation with handgrip by Spearman.Results. There were 52 subjects completed all examinations, received radiotherapy ≥25 times combination chemotherapy, 57% male, 50 years old. Most sites at nasopharynx, mostly stage IV, 25% subjects had normal body mass indeks, 75% were low. Most subjects had nutritional problems caused by inadequate intake of energy, protein, fat, and omega-3 fatty acids. Majority (75%) had small muscle mass (28.4±4.7%), mostly (75%) normal handgrip, median 37.1(25.7‒68.5) kg, and all subjects had very low omega-3 fatty acids plasma (2.5±0.8%). There was strong correlation between omega-3 fatty acids plasma with muscle mass (r =0.6, p <0.05) and handgrip (r =0.8, p <0.001) who received radiotherapy  (>60–70 Gy), no correlation less than that doses.Conclusion. There was correlation between omega-3 fatty acids plasma with muscle mass and handgrip, at radiotherapy doses >60–70 Gy.